Chemical constituents of theessential oils of Pimpinella anisum L. and Cuminum Cyminum L. - 463472 Noor Aziella Shamsuddin; Hasnah Mohd. Sirat, supervisor; Fakulti Sains (2007)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2007